Les rencontres entre communautés dans l’Acre latine du xiiie siècle : l’exemple de Saliba, marchand et bourgeois - Florian Besson (Bulletin du Centre d’Études Médiévales d’Auxerre)
In 1264, Saliba, a Syrian and a burgess of Acre, capital of the latin kingdom of Jerusalem, dictates his will. This document reveals the complexity of his identity : he works with oriental merchants – Jews, Armenians, Damascenes, Mongols, etc – and at the same time with Italians ones, in particular with Genoese. His legacy to various religious instititions shows that he is probably a Catholicism convert ; the first names of his family members highlight an oriental family who is partially occidentalized. Saliba is therefore a good example through which we can think about the meetings and interactions between religious and ethnic communities in Latin East.